Performance of concrete with rice husk waste under different environments - Muhammad Adib, Ismail (2012)
Nowadays, the utilization of unwanted materials to be added into concrete mix to improve its performance is continuously studied by many researchers. A study has been conducted in the laboratory to investigate the performance of concrete with rice husk waste under different environments. A number of 60 cubes, 100 mm x 100 mm x 100 mm were prepared with 30 cubes as a control and another group of 30 cubes containing rice husk waste. All these samples were left under various environments for 7 and 28 days. The environments were acidic, alkaline, outdoor, clean water and indoor environment. The performance of concrete samples was monitored through their compressive strength at 7 and 28 days. The results obtained indicated that the strength of concrete with rice husk wastes have decreased at all ages and environments by almost half of the strength of the normal concrete cubes.